The Role of Native English-Speaking Teachers in Improving Students’ Speaking Skills - Herlina, Lina; Said, Mashadi (Advances in Social Sciences Research Journal, 2022)
This study was conducted to determine whether (1) native English-speaking teachers can increase students’ learning motivation in speaking skills, (2) English-speaking teachers can improve students’ achievement in spoken English, (3) there is a significant difference in learning achievement between students who are taught by English-speaking teachers and those who are taught by non-native-speaking teachers. This study used a mix of quantitative and qualitative research techniques. Quantitative data was obtained from speaking skill tests with predetermined criteria, while qualitative data was obtained from a questionnaire that is adopted from [1]. A total of 80 students from class XI of a public high school in Sukabumi Regency Indonesia participated in this study. The results show that native English-speaking teachers can increase students’ learning motivation in speaking skills. They can also improve the students’ achievement in spoken English, and there is a significant difference in learning achievement between students who are taught by English-speaking teachers and those who are taught by non-native-speaking teachers. This implies that English-speaking teachers play a very important role in improving students’ motivation and in developing students’ achivement.